1998
DOI: 10.1086/515260
|View full text |Cite
|
Sign up to set email alerts
|

Serotype Distribution of Invasive Group B Streptococcal Isolates in Maryland: Implications for Vaccine Formulation

Abstract: Invasive group B streptococcal (GBS) infection is a major health problem among infants and adults. The formulation of GBS vaccines depends on knowledge of the GBS serotype distribution. Serotype V GBS infection appears to have recently emerged, suggesting that the serotype distribution changes over time. GBS isolates from 210 pediatric patients, 23 pregnant women, and 314 nonpregnant adults with invasive infection in Maryland were studied. The predominant serotypes from infants with early-onset disease were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
137
1
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 14 publications
26
137
1
8
Order By: Relevance
“…French reports indicate that serotype V accounted for about 15% of isolates recovered from neonates (1,16). Similar proportions (14 and 12%) of serotype V strains causing invasive infections were observed in neonates from Atlanta (6) and Maryland (13).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…French reports indicate that serotype V accounted for about 15% of isolates recovered from neonates (1,16). Similar proportions (14 and 12%) of serotype V strains causing invasive infections were observed in neonates from Atlanta (6) and Maryland (13).…”
supporting
confidence: 62%
“…Recently, serotype V GBS have emerged as a new cause of GBS infection or colonization in children and adults (13,18,19). Indeed, population-based surveillance of GBS in the 1990s indicated that serotype V was responsible for 10 to 15% of neonatal GBS infections in the United States (7,13,17) and was the most common serotype isolated from nonpregnant adults with invasive disease (13). Moreover, data from the Centers for Disease Control and Prevention (Atlanta, Ga.) have shown the emergence of a serotype V clonal type (8).…”
mentioning
confidence: 99%
“…Several serotypes of GBS exist (9), but only a few (serotypes Ia, Ib, Ic, II, and III) are common causes of human disease. Over the past decade, several investigators reported an increasing proportion of GBS disease to be due to serotype V (GBS-V) (1,2,8,11,21).…”
Section: Pulsed-field Gel Electrophoresis (Pfge) Was Performed On 122mentioning
confidence: 99%
“…There are major differences between countries in the distribution of GBS serotypes. In the USA, Germany and Sweden, the most common serotypes isolated from infants and colonized mothers have been types Ia, III, and V (Persson et al, 2004;Brimil et al, 2006;Harrison et al, 1998). Serotype V strains emerged in the 1990s as a frequent cause of neonatal sepsis and adult diseases in the USA.…”
mentioning
confidence: 99%